The Effect of the Tourism Sector on Labor Absorption in Indonesia - Annisa Azhar; Silvia Dwi Aryanti; Yoga Pratama; Dodi Tirtana (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2025)
This study will analyze the factors influencing employment in the Indonesian tourism sector in 2021-2022. The independent variables used include the number of foreign guests staying in star hotels, the average duration of stay of foreign guests, and the room occupancy rate, while the number of tourism sector workers is the dependent variable. Data were obtained from Statistics Indonesia and the Ministry of Tourism and Creative Economy, covering 34 provinces. The analysis was conducted using multiple linear regression methods on panel data with FEM (Fixed Effect Model) approach to test the relationship between variables. The results showed that the number of foreign guests, the average length of stay, and the room occupancy rate all significantly affected employment simultaneously. While partially, the number of foreign guests and the room occupancy rate have a positive and significant effect, the average duration of stay has no considerable effect. This finding confirms that an increase in the number of foreign guests and the room occupancy rate can boost employment growth in the tourism sector. Therefore, strategies to attract more tourists and increase hotel occupancy must be strengthened to create more jobs.